2019
DOI: 10.3390/ijerph16234719
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Smoking among Gambian Men: A Cross-Sectional National WHO STEP Survey

Abstract: Background: Tobacco use is the leading cause of preventable death in the world, with a higher burden in low- and middle-income countries. The aim of this study was to quantify the prevalence and predictors of smoking among Gambian men using nationally representative data. Methods: Data was collected in 2010 from a random, nationally representative sample of 4111 adults aged 25–64 years (78% response rate) using the World Health Organization (WHO) STEPwise cross-sectional survey methods. Our analyses focused on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…In addition, the results are used by the Ministry of Health of The Gambia in their routine sensitisation campaigns. Like our previous analyses, 19 20 the results of this study will be shared with the public and will also be used to inform policy.…”
Section: Patient and Public Involvementmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the results are used by the Ministry of Health of The Gambia in their routine sensitisation campaigns. Like our previous analyses, 19 20 the results of this study will be shared with the public and will also be used to inform policy.…”
Section: Patient and Public Involvementmentioning
confidence: 92%
“…19 There is also a high prevalence of smoking among Gambian men. 20 Moreover, these health risks have significant implications for wider development concerns. It poses a barrier to poverty alleviation and can hinder the attainment of the United Nations Sustainable Development Goals, particularly target 3.4, which calls for a reduction in premature mortality due to NCDs by one-third by 2030.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted among the Gambian men reported that 31.4% of men aged 25-64 years old smoked tobacco in 2010. 12 Another study carried out in this country among students aged 12-20 years old found that 16.7% of students consumed tobacco in 2016. 13 Nevertheless, the prevalence of and factors associated with tobacco smoking based on up-to-date data among both men and women and nationally representative data were not available in The Gambia.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 95%
“…Smoking cigarettes constitutes a behavior that can start in adolescence and persist throughout life, leading to many social, physical, and economic consequences ( 52 ). Accordingly, global measures, including monitoring tobacco use; implementing prevention policies, such as public health interventions, individual and group counseling, behavioral support, and pharmacotherapy ( 53 ); protecting people from secondhand smoke; providing assistance and instruments to quit tobacco use; enforcing bans on tobacco advertising; promoting and sponsoring tobacco cessation campaigns; and raising taxes on cigarettes ( 4 , 10 , 54 ) have been deployed to promote cigarette smoking cessation. In Brazil, there are a large number of preventive campaigns focused on the risks of smoking and laws limiting the use of tobacco in public places and prohibiting access to and the consumption of tobacco products by those under the age of 18, although these restrictions are not respected or enforced by all merchants ( 13 ), as evidenced by a survey of 748 adolescents in Brazil, among whom 80.3% of those who smoked reported having easy access to cigarettes ( 20 ).…”
Section: Discussionmentioning
confidence: 99%